Connie : a memoir [large type] - Chung, Connie, 1946- (Thorndike Press large print top shelf., 2024)
"Profoundly influenced by her family's cultural traditions, yet growing up completely Americanized in the United States, Chung describes her career as an Asian woman in a white male-centered world. Overt sexism was a way of life, but Chung was tenacious in her pursuit of stories - battling rival reporters to secure scoops that ranged from interviewing Magic Johnson to covering the Watergate scandal - and quickly became a household name. She made history when she achieved her dream of being the first woman to co-anchor the CBS Evening News and the first Asian to anchor any news program in the U.S"--Provided by publisher.